Symmetric Subsets and Colorings of Connected Compact Groups - Banakh, T. O. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We find upper and lower bounds for the Haar measure of a monochromatic symmetric subset, which can be found in every measurable r-coloring of a connected compact group.